Solution processable diketopyrrolopyrrole (DPP) cored small molecules with BODIPY end groups as novel donors for organic solar cells - Cortizo-Lacalle, Diego; Howells, Calvyn T.; Pandey, Upendra K.; Cameron, Joseph; Findlay, Neil J.; Inigo, Anto Regis; Tuttle, Tell; Skabara, Peter J.; Samuel, Ifor D. W. (Beilstein Journal of Organic Chemistry, 2014)
Two novel triads based on a diketopyrrolopyrrole (DPP) central core and two 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY) units attached by thiophene rings have been synthesised having high molar extinction coefficients. These triads were characterised and used as donor materials in small molecule, solution processable organic solar cells. Both triads were blended with PC71BM as an acceptor in different ratios by wt % and their photovoltaic properties were studied. For both the triads a modest photovoltaic performance was observed, having an efficiency of 0.65%. Moreover, in order to understand the ground and excited state properties and vertical absorption profile of DPP and BODIPY units within the triads, theoretical DFT and TDDFT calculations were performed.
Keywords: BODIPY; diketopyrrolopyrrole; organic semiconductors; organic solar cells; thiophene